ESHRE Guideline: management of women with premature ovarian insufficiency - European Society for Human Reproduction and Embryology (ESHRE) Guideline Group on POI; Webber, L; Davies, M; Anderson, R; Bartlett, J; Braat, D; Cartwright, B; Cifkova, R; de Muinck Keizer-Schrama, S; Hogervorst, E; Janse, F; Liao, L; et al. (Human reproduction (Oxford, England), 2016)
STUDY QUESTION: What is the optimal management of women with premature ovarian insufficiency (POI) based on the best available evidence in the literature? SUMMARY ANSWER: The guideline development group (GDG) formulated 99 recommendations answering 31 key questions on the diagnosis and treatment of women with POI. WHAT IS KNOWN ALREADY: NA. STUDY DESIGN, SIZE, DURATION: This guideline was produced by a multidisciplinary group of experts in the field using the methodology of the Manual for ESHRE Guideline Development, including a thorough systematic search of the literature, quality assessment of the included papers up to September 2014 and consensus within the guideline group on all recommendations. The GDG included a patient representative to ensure input from women with POI. After finalization of the draft, the European Society for Human Reproduction and Embryology (ESHRE) members and professional organizations were asked to review the guideline. PARTICIPANTS/MATERIALS, SETTING, METHODS: NA. MAIN RESULTS AND THE ROLE OF CHANCE: The guideline provides 17 recommendations on diagnosis and assessment of POI and 46 recommendations on the different sequelae of POI and their consequences for monitoring and treatment. Furthermore, 24 recommendations were formulated on hormone replacement therapy in women with POI, and two on alternative and complementary treatment. A chapter on puberty induction resulted in five recommendations. LIMITATIONS, REASONS FOR CAUTION: The main limitation of the guideline is that, due to the lack of data, many of the recommendations are based on expert opinion or indirect evidence from studies on post-menopausal women or women with Turner Syndrome. WIDER IMPLICATIONS OF THE FINDINGS: Despite the limitations, the guideline group is confident that this document will be able to guide health care professionals in providing the best practice for managing women with POI given current evidence. Furthermore, the guideline group has formulated research recommendations on the gaps in knowledge identified in the literature searches, in an attempt to stimulate research on the key issues in POI. STUDY FUNDING/COMPETING INTERESTS: The guideline was developed and funded by ESHRE, covering expenses associated with the guideline meetings, with the literature searches and with the implementation of the guideline. The guideline group members did not receive payment. Dr Davies reports non-financial support from Novo Nordisk, outside the submitted work; the other authors had nothing to disclose. TRIAL REGISTRATION NUMBER: NA.
Keywords: premature ovarian insufficiency; Female; Societies, Scientific; Primary Ovarian Insufficiency; Humans; Hormone Replacement Therapy; dospělí; společnosti vědecké; ženské pohlaví; evidence based; hormonální substituční terapie; POI; mladiství; lidé; guideline; primární ovariální insuficience; puberta; Adolescent; Adult; Puberty; European Society of Human Reproduction and Embryology